1993
DOI: 10.1007/bf02928172
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and pattern of impaired reading and written language in children with attention deficit disorders

Abstract: The purpose of this study was to investigate the occurrence and severity of reading, spelling, and written language impairment in children clinically referred for Attention Deficit Hyperactivity Disorder (ADHD). Specific questions involved 1) whether ADD subgroups with and without hyperactivity differ in reading, spelling, and written language achievement, 2) whether age and gender interact with ADD sub-group class to affect reading/written language achievement, and 3) whether prevalence of impaired reading/wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…• Specific Language Impainnent (Hill (1998); Powell & Bishop (1992);Elbert (1993), Powell & Bishop (1992)). …”
Section: Prevalence Rates In Child and Adulthoodmentioning
confidence: 99%
“…• Specific Language Impainnent (Hill (1998); Powell & Bishop (1992);Elbert (1993), Powell & Bishop (1992)). …”
Section: Prevalence Rates In Child and Adulthoodmentioning
confidence: 99%
“…Thus, Wood and Felton concluded that ADHD may impair long-term outcome to a greater extent than it impairs reading acquisition (Wood & Felton, 1994). This more global pattern of low achievement in children diagnosed as ADHD has also been found in other studies (e.g., Elbert, 1993).…”
Section: Separation Of Attention-reading Difficultymentioning
confidence: 80%
“…A number of studies have focused on phonological processing and word attack skills (e.g., Ackerman & Dykman, 1993;Elbert, 1993;Hynd et al, 1995;Pennington, et al, 1993;Wood & Felton, 1994), rapid naming (e.g., Ackerman & Dykman, 1993;Felton, Wood, Brown, Camp- Kupietz (1990) Robbins (1992) Ackerman & Dykman Deficits in rapid naming were found to be associated with RD; deficits in verbal rote learning and memory were found to be associated with ADHD; no specific effects were found to be attributable to RD with ADHD. Children in the RD group demonstrated significant deficits on recall of verbal items.…”
Section: Separation Of Attention-reading Difficultymentioning
confidence: 96%
See 2 more Smart Citations